The Managerial Mechanism of Social Sphere Future Specialists' Professional World View Formation - Valeyeva, Nailya Sh.; Kupriyanov, Roman V.; Valeyeva, Elvira R.; Nadeyeva, Marina I.; Guryanova, Tatyana N.; Yurtayeva, Natalya I.; Kaysarova, Zhanna E.; Safina, Albina A. (International Review of Management and Marketing, 2016)
The relevance of the study is reasoned by the modernization of professional education of social sphere's specialists, the leading strategy of which is formation of professional worldview as a system of professional ideals, intellectual and moral-emotional attitude to professional activities, readiness for life-long learning, self-organization and competitiveness on the labor market. Professional worldview as a system of internal determinants of human life leads to a reflexive and reasoned choice of value-activities orientations and life-affirming priorities. The purpose of this paper is to develop a managerial mechanism to form world view of the future specialist of social sphere. The leading method is the method of action research (AR), allowing to obtain new knowledge on the essence and structure of professional worldview, to identify the steps, to define principles, to clarify the objectives, methods, pedagogical conditions, criteria of formation of professional worldview of future specialists of social sphere. The paper reveals the essence and structure of professional world view, including epistemological (cognitive), axiological (values), congruent (principles, beliefs, orientation), praxes-logical (practice) components; identifies the stages (adaptive, explicit, productive) and defines principles of (creativity, acme-logical, the actuality, the subjective integration, comparatives) formation of professional worldview; refines objectives (the integration of the content of training; strengthening of integrative cooperation of vocational schools with social centers; proposes the development of scientific and methodological support of students' professional identification) clarifies methods (cognitive, motivational, professional activities), reveals teaching conditions (readiness of teachers to formation of students' professional worldview; integration of general and professional knowledge; project-oriented form of vocational training), identifies criteria (cognition, axiological, congruence, praxis-logical) of social sphere future specialists' professional world view formation. The paper submissions can be useful for teachers of research universities, which train specialists for the social sphere; for centers of advanced training and retraining of personnel in the selection and structuring of the content for the advanced training of specialists of social sphere and science staff at research universities. Keywords: Professional Worldview, Professional Education, Specialists of Social Sphere, Management. JEL Classifications: A20, I21, I28